Narrative Review of the Pharmacodynamics, Pharmacokinetics, and Toxicities of Illicit Synthetic Cannabinoid Receptor Agonists - Lea Houston, Matilda; Morgan, Jody; Kelso, Celine (Mini Reviews in Medicinal Chemistry, 2024)
Background: Synthetic cannabinoid receptor agonists (SCRAs) are the most diverse class of new psychoactive substances worldwide, with approximately 300 unique SCRAs identified to date. While the use of this class of drug is not particularly prevalent, SCRAs are associated with several deaths every year due to their severe toxicity. Methods: A thorough examination of the literature identified 15 new SCRAs with a significant clinical impact between 2015 and 2021. Results: These 15 SCRAs have been implicated in 154 hospitalizations and 209 deaths across the US, Europe, Asia, and Australasia during this time period. Conclusion: This narrative review provides pharmacodynamic, pharmacokinetic, and toxicologic data for SCRAs as a drug class, including an in-depth review of known pharmacological properties of 15 recently identified and emerging SCRAs for the benefit of researchers, policy makers, and clinicians who wish to be informed of developments in this field.
Keywords: spice